(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This article examines the relationship between organizational-technological modeling and energy consumption in the construction of low-rise residential buildings. The study focuses on how different organizational and technological approaches can impact energy efficiency and overall sustainability in the construction process. Various factors such as building materials, construction methods, and energy systems are analyzed to determine their contribution to energy consumption in low-rise residential buildings. The findings suggest that implementing sustainable practices and technologies can significantly reduce energy consumption and environmental impact during the construction phase.